Une conception sociale cognitive de l’orientation scolaire et professionnelle : considérations théoriques et pratiques - W. Lent, Robert (L'orientation scolaire et professionnelle, 2008)
This article describes social cognitive career theory (SCCT), a recent effort to extend Bandura’s (1986) general social cognitive theory to the domain of career development. SCCT focuses on the processes through which people (a) develop educational and vocational interests, (b) make academic and career-related choices, and (c) achieve performances of varying quality in their educational and occupational pursuits. SCCT incorporates variables (e.g., self-efficacy, goals) that enable people to influence their own career development, as well as variables (e.g., environmental barriers, support systems) that weaken or strengthen the exercise of personal control over one’s career path. In addition to providing an overview of SCCT, this article discusses the theory’s research base and implications for developmental and remedial interventions.